2017
DOI: 10.18632/oncotarget.15518
|View full text |Cite
|
Sign up to set email alerts
|

Trichosanthin increases Granzyme B penetration into tumor cells by upregulation of CI-MPR on the cell surface

Abstract: Trichosanthin is a plant toxin belonging to the family of ribosome-inactivating proteins. It has various biological and pharmacological activities, including anti-tumor and immunoregulatory effects. In this study, we explored the potential medicinal applications of trichosanthin in cancer immunotherapy. We found that trichosanthin and cation-independent mannose-6-phosphate receptor competitively bind to the Golgi-localized, γ-ear containing and Arf-binding proteins. It in turn promotes the translocation of cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…GGA contains four structural functional domains, of which the N-terminal Vps, Hrs and STAM (VHS) domain can bind to DXXLL motifs of cargo proteins and was confirmed in our study to directly interact with TCS [7] . TCS then can competitively inhibit cation-independent mannose 6-phosphate receptors (CI-MPRs), a transmembrane glycoprotein, binding to GGA.…”
Section: Research Highlightsupporting
confidence: 75%
See 2 more Smart Citations
“…GGA contains four structural functional domains, of which the N-terminal Vps, Hrs and STAM (VHS) domain can bind to DXXLL motifs of cargo proteins and was confirmed in our study to directly interact with TCS [7] . TCS then can competitively inhibit cation-independent mannose 6-phosphate receptors (CI-MPRs), a transmembrane glycoprotein, binding to GGA.…”
Section: Research Highlightsupporting
confidence: 75%
“…Our recently published study used pull down assay and identified TCS binds with Golgi-localized, γ-ear containing and Arf-binding proteins (GGA) proteins in HepG2 cells [7] . GGA contains four structural functional domains, of which the N-terminal Vps, Hrs and STAM (VHS) domain can bind to DXXLL motifs of cargo proteins and was confirmed in our study to directly interact with TCS [7] .…”
Section: Research Highlightmentioning
confidence: 99%
See 1 more Smart Citation
“…TCS mediated Phosphoinositide 3-kinase (PI3K)/Protein kinase B (AKT) pathway and thus enhanced cytotoxicity and apoptosis-inducing activity of an anti-cancer therapy Gemcitabine against non-small cell lung cancer [56]. TCS also enhanced the cell penetration of Granzyme B leading to apoptosis of tumor cells [57]. It was shown that TCS incited autophagy in gastric cancer cells via increasing the level of autophagy protein 5 (ATG5), altering microtubule-associated protein 1A/1B-light chain 3 (LC3) I to LC3 II, inducing reactive oxygen species (ROS) and stimulating nuclear factor kappa-B (NF-κB)/Tumor protein p53 (p53) pathway [58].…”
Section: Anti-tumor Activity Of Representative Ripsmentioning
confidence: 99%
“…Trichosanthin is also a plant toxin belonging to the family of ribosome-inactivating proteins. It has various biological and pharmacological activities, including anti-tumor and immunoregulatory effects 149 . It has dose-dependent inhibitory effect on the invasion, migration and proliferation of human glioma cells and can induce tumor cell apoptosis by the inhibition of WNT/ β -catenin signal pathways 150 .…”
Section: Natural Products Regulating the Bbb Microenvironmentmentioning
confidence: 99%